Antimicrobial susceptibility pattern and phenotypic detection of metallo-beta lactamases in K. pneumoniae isolates in a tertiary care hospital - Paray, Ansar Ahmad; Kaur, Amandeep (International Journal of Research in Medical Sciences, 2022)
Background: K. pneumoniae is the most important pathogen causing community as well as nosocomial infections. The study was conducted with the aim to study antimicrobial susceptibility pattern of K. pneumoniae isolates as well as to detect MBL in carbapenem resistant isolates. Methods: The study was conducted for a period of six months from October 2021 to March 2022. All isolates of K. pneumoniae were obtained from various clinical samples. Antimicrobial susceptibility testing was done by Vitek 2 Compact system. Metallo β-lactamase detection was done by imipenem-EDTA combined disk method. Results: Out of total 1336 growth positive isolates, 248 isolates were of K. pneumoniae. From total 248 isolates, 162 were obtained from male patients and 86 were obtained from female patients. Maximum number (97) of isolates was obtained from age group of 61-80 years. Maximum (30.24%) isolates of K. pneumoniae were from urine and minimum (4.43%) from body fluids. Isolates were highly resistant towards antimicrobials tested whereas moderate sensitivity was reported for ertapenem, imipenem, meropenem and gentamicin. Isolates were highly sensitive to colistin followed by amikacin and tigecycline. MBL production was observed in 84.5% carbapenem resistant isolates. Conclusions: This present study highlighted that multidrug resistant strains of K. pneumoniae are common in tertiary care hospitals. Unwarranted and unrestricted usage of antimicrobials is associated with growing emergence of resistance. Therefore, regular monitoring of carbapenem resistance is important for developing strategies to control infections caused by K. pneumoniae.